La migración como escenario para la comprensión de la violencia de género entre migrantes internacionales - Marcela Tapia Ladino (Les Cahiers ALHIM)
Gender related violence between migrants is still a subject little analyzed on migratory researches. This article seeks how often domestic violence occurs between the migratory couples taking into account reception through case consideration. Characterization of the origin and destination contexts, as well as the type of relationship between the predominating couple before migration, previous work experience, migratory pattern and different occupational experiences in relation to destination context are some of the aspects which explain cruel treatment and physical violence. We postulate that this phenomenon is not separated from what happens in their original society nor either it implies its absence in the destination context just because there is an institutional framework which protects  migratory women’s rights.